Morel-Lavallee lesion: a forgotten cause of bleeding in trauma - Khor, CC; Tan, Toh Leong (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
The Morel-Lavallee lesion is a rare soft tissue injury that occurs due to traumatic shearing force on skin surface causing separation of skin and subcutaneous tissue resulting in hematoma. This case report depicts a 22-year-old gentleman who was involved in a motor vehicle accident. He complained of pain and swelling over lower back. He was treated for soft tissue injury and admitted for pain control. One day post-trauma, he complained of increased swelling over the back. His hemoglobin dropped from 12.2g/dL to 10.7g/dL. Diagnosis of Morel-Lavallae lesion was made. Initially no surgical intervention was planned. However, in view of worsening of swelling, bedside aspiration was performed and subsequently a pigtail catheter was inserted to drain the hematoma. In total, 2.05 litre of liquefied hematoma was drained. Thus, Morel-Lavallee lesion is an uncommon soft tissue injury that can cause significant bleeding following trauma.